Sistem Musaqah Pada Perkebunan Kelapa Dalam Prespektif Hukum Ekonomi Syaria’ah (Studi Kasus di Desa Habunuha Kecamatan Tabona Kabupaten Pulau Taliabu) - Jaini, Meliani La; Darmawangsa, Andi; Zainal, Abdul Qahar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the Musaqah system in coconut plantations in Habunuha Village, Tabona Subdistrict, Pulau Taliabu Regency, and to evaluate its conformity with the principles of Sharia Economic Law. In practice, the Musaqah system in Habunuha is implemented orally, based on mutual trust and local customs, without any formal written agreement. This research uses a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation.The findings indicate that the Musaqah practice carried out by the community in Habunuha is based on trust and kinship. However, there are still several shortcomings in terms of legal clarity, such as the absence of written contracts and the lack of formally documented profit-sharing mechanisms. The profit-sharing arrangement used in Habunuha is 1:1 between landowners and cultivators, with operational costs shared equally. The study recommends the need for Sharia literacy education for the community and more formal regulatory support to ensure that the Musaqah system can operate more optimally and in accordance with Sharia Economic Law.